# 5

1.2: KNOW INVERSE HYPERBOLIC FUNCTIONS

1.2.1: Define Inverse Hyperbolic Function

- The inverses of the hyperbolic functions are the area hyperbolic functions.
- Form of sinh
-1
, cosh
-1
, tanh
-1
, cosech
-1
, sech
-1
and coth
-1

- The inverse hyperbolic functions are given by:
i. y = tanh
-1
x → x = tanhy
ii. y = sinh
-1
x → x = sinhy
iii. y = cosh
-1
x → x = coshy
iv. y = coth
-1
x → x = cothy
v. y = cosech
-1
x → x = cosechy
vi. y = sech
-1
x → x = sechy

1.2.2: CalculateValues of Inverse Hyperbolic Functions

- Example (d)
Find to 4 decimal places:
i. cosh
-1
(2.364)
ii. tanh
-1
(-0.322)
iii. sinh
-1
x = ln 2

Solution:
i. cosh
-1
(2.364)
Step 1: Identify the formula
|
.
|

\
|
÷ + ± =
÷
1 ln
2 1
x x x cosh
Step 2: Replace the value of x into the formula
x = 1.275 → ( ) |
.
|

\
|
÷ + ± =
÷
1 364 . 2 364 . 2 ln 364 . 2
2 1
cosh

= () = 1.5054

ii. tanh
-1
(-0.322)
(
¸
(

¸

÷
+
=
÷
x
x
x tanh
1
1
ln
2
1
1

FORMULA:
-
|
.
|

\
|
+ + =
÷
1 ln
2 1
x x x sinh
-
|
.
|

\
|
÷ + ± =
÷
1 ln
2 1
x x x cosh
-
(
¸
(

¸

÷
+
=
÷
x
x
x tanh
1
1
ln
2
1
1

-
(
(
¸
(

¸

÷ +
=
÷
x
x
x sech
2
1
1 1
ln
-
(
(
¸
(

¸

+
+ =
÷
x
x
x
x cosech
2
1
1 1
ln
-
1
1
ln
2
1
1
÷
+
=
÷
x
x
x coth
6

(
¸
(

¸

÷ ÷
÷ +
= ÷
÷
) 322 . 0 ( 1
) 322 . 0 ( 1
ln
2
1
322 . 0
1
tanh

() = -0.3339

iii. sinh
-1
x = ln 2
( √

)
( √

)
(√

)
x
2
+ 1 = 4 – 4x + x
2

x = 0.75

1.2.3: Sketch The Graphs of Inverse Hyperbolic Functions

HYPERBOLIC FUNCTIONS GRAPH
sinh
-1

cosh
-1

tanh
-1

Try this!
1. Evaluate:
a) cosech
-1
(

)
b) coth
-1
(5)
2. Prove that:
|
.
|

\
|
+ + =
÷
1 ln sinh
2 1
x x x

HYPERBOLIC FUNCTIONS GRAPH
cosech
-1

sech
-1

coth
-1

7

- Example (e)
Sketch the graph of y = sinh
-1
x from point x = -30 to x = 30

Solution:
Step 1: Create table from start point to end point (using calculator)
x -30 -10 0 10 30
y -4 -3 0 3 4

Step 2: Sketch graph by referring to the table

1.2.4: Derive The Formulae of Inverse Hyperbolic Functions

- Since the hyperbola functions are in essence exponential functions you should expect their inverses to involve the natural logarithm.
- Example (f)
Prove that sinh
-1
x = ln( √

)

Solution:

Step 1: Switch the equation
y = sinh
-1
x → x = sinhy

Step 2: Choose formula from page 1 (unit 1.1) and simplify
2
sinh
y y
e e
y x
÷
÷
= =

y y
e e
÷
÷

Step 3: Multiply with e
y

(

) (
y y
e e
÷
÷ )

-3
4
-4
4
4
4
3
4
10 30 -30 -10
Try this!
Sketch graphs for below functions:
a) y = sech
-1
x from point x = 0.1 to x = 1
b) cosh
-1

8

Step 4: Use the Quadratic Formula to solve this quadratic-like equation.

a =1 , b = -2x , c = -1 , x = e
y

√()

()()
()

= √

Step 5: Simplify using logarithm law

( √

)
( √

)→ sinh
-1
x = ln( √

) Proved!

Try this!
Verify that:
a)

for||
b)
|
.
|

\
|
÷ + ± =
÷
1 ln cosh
2 1
x x x

Sign up to vote on this title